EXPLORING THE DISTINCTIVE FEATURES OF INDONESIAN TAFSIR AL-QURAN: A STUDY OF SHEIKH ABDUL LATIF SYAKUR'S AD-DA'WAH WA AL-IRSYĀD ILĀ SABĪLI AR-RASYĀD - Romadhona, Azizah; Apriantoro, Muhamad Subhi; Rasyid, Laila Muhammad (QiST: Journal of Quran and Tafseer Studies, 2024)
Tafsir Al-Quran Indonesia has its own characteristics. The Koran interpretation struggles with the guide's traditions and culture. One of the exciting interpretations is ad-Da'wah wa al-Irsyād ilā Sabīli ar-Rasyād, written by Sheikh Abdul Latif Syakur. This paper attempts to explain the biography of Sheikh Abdul Latif Syakur, his methodology of interpretation, as well as the Indonesian side of his interpretation. This research is library research and is qualitative. The results showed that Sheikh Abdul Latif Syakur was a Minangkabau cleric who studied in Makkah from childhood to adulthood. This interpretation is a thematic interpretation of phrases that collect verses with the prefix wa min an-Nās, characterized by Ijtima'i adab. This interpretation also has an Indonesian side.